Detection of Helicobacter pylori in the Gastric Mucosa by Fluorescence In Vivo Hybridization - Sílvia J. Fontenete (2017)
In this chapter, we describe a fluorescence in vivo hybridization (FIVH) protocol, using nucleic acid probes, for the detection of the bacterium Helicobacter pylori in the gastric mucosa of an infected C57BL/6 mouse model. This protocol should be easily extended to other microorganisms not only as a way to identify in vivo important microorganisms and their patterns of distribution within specific or at different anatomic sites, but also to better understand interaction mechanisms involving the microbiome and the human body.